Towards Targeted Alpha Therapy with Actinium-225: Chelators for Mild Condition Radiolabeling and Targeting PSMA-A Proof of Concept Study - Reissig, Falco; Bauer, David; Zarschler, Kristof; Novy, Zbynek; Bendova, Katerina; Ludik, Marie-Charlotte; Kopka, Klaus; Pietzsch, Hans-Jürgen; Petrik, Milos; Mamat, Constantin (Cancers, 2021)
Currently, targeted alpha therapy is one of the most investigated topics in radiopharmaceutical cancer management. Especially, the alpha emitter 225Ac has excellent nuclear properties and is gaining increasing popularity for the treatment of various tumor entities. We herein report on the synthesis of two universal 225Ac-chelators for mild condition radiolabeling and binding to conjugate molecules of pharmacological interest via the copper-mediated click chemistry. A convenient radiolabeling procedure was investigated as well as the complex stability proved for both chelators and two PSMA (prostate-specific membrane antigen)-targeting model radioconjugates. Studies regarding affinity and cell survival were performed on LNCaP cells followed by biodistribution studies, which were performed using LNCaP tumor-bearing mice. High efficiency radiolabeling for all conjugates was demonstrated. Cell binding studies revealed a fourfold lower cell affinity for the PSMA radioconjugate with one targeting motif compared to the radioconjugate owing two targeting motifs. Additionally, these differences were verified by in vitro cell survival evaluation and biodistribution studies, both showing a higher cell killing efficiency for the same dose, a higher tumor uptake (15%ID/g) and a rapid whole body clearance after 24 h. The synthesized chelators will overcome obstacles of lacking stability and worse labeling needs regarding 225Ac complexation using the DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayl)tetraacetic acid) chelator. Moreover, the universal functionalization expands the coverage of these chelators in combination with any sensitive bio(macro)molecule, thus improving treatment of any addressable tumor target.
Keywords: theranostics; click chemistry; actinium-225; PSMA; targeted alpha therapy